Strategiczne partnerstwo Unia Europejska-Indie – w oczekiwaniu na przełom - Potyrała, Anna (Przegląd Strategiczny, 2011)
On August 1, 1994 the Cooperation Agreement between the European Community and the Republic of India on partnership and development entered into force. On June 16, 2004, in the tenth anniversary of the partnership, the European Commission presented the communication „An EU-India Strategic Partnership” in order to intensify cooperation with India. The Republic of India was regarded as a regional and global leader, being able to have equal relations with EU members. This paper is to analise signs of cooperation aimed at stategic partnership, and to present that despite legal and institutional frameworks of cooperation, no comprehensive concept of partnership was implemented. Moreover, years of relations have showned that partners are not equal, as well as that course and speed of cooperation are shaped unilaterally by the European Union.